A new species of Russula (Russulales) from Eastern Himalaya, India - Paloi, Soumitra; Dutta, Arun Kumar; Acharya, Krishnendu (Phytotaxa, 2015)
A new species of Russula (Russulaceae, Basidiomycota) is described from Darjeeling Hill, Eastern Himalaya, India. Morphological and molecular (nuclear ribosomal internal transcribed spacer region) sequence data assign the present species to the subgen. Incrustatula Romagn., sect. Lilaceinae (Melzer & Zvára) Konrad & Joss. and subsect. Lilaceinae Melzer & Zvára. Comprehensive description, photographs and comparisons with morphologically similar and phylogenetically related species are provided.